Electron transfer quenching studies of luminescent complex’s of Ru (iii) with mixed ligands - Tripathi, P N; Verma, Smriti; Singh, R P (Journal of Experimental Sciences, 2012)
In the present paper the reaction of Ru (III) perchlorates with some polytertiary phosphines and arsines has been investigated. The study of quenching of excited states of Ru (LL’-)33+ complexes and subsequent reaction occuring with potential reductant - amines, aromatic ether, nitro compounds, p-hydroquinone and water have been observed. Both laser flash and convensional spectroscopic techniques have been used to monitor the quencher products. The photo reduction of complex (I) with triethylamine can be shown to consists of two component, a primary photoprocess and a subsequent dark reaction while for complex (II) only the first process is observed. The reduced complex Ru (LL’)+23 produced in the reaction are relatively stable and dry deacrated solution but can be observed rapidly with both oxygen and water. The reaction of reduced (I) with water is a relatively produce Ru (LL’) +3H+2 which yields hydrogen and to starting. Complex (I) with colloidal platinum excited states of (I) are also quenched by aromatic ether and hydroquionones in process giving transients having spectra similar to that the reduced (I). The reaction between excited (I) with water (K = 1x 107M-1 S-1) gives a short lifed transient (ïŠ= 245ns) more lightly an adduct or ligand protonated species more lightly and adduct or ligand protonated species.